Recognition of beta 2-microglobulin-negative (beta 2m-) T-cell blasts by natural killer cells from normal but not from beta 2m- mice: nonresponsiveness controlled by beta 2m- bone marrow in chimeric mice. - Höglund, P (1991)
The role of major histocompatibility complex (MHC) class I expression in control of the sensitivity of normal cells to natural killer (NK) cells was studied by the use of mutant mice made deficient for expression of beta 2-microglobulin (beta 2m) through homologous recombination in embryonal stem cells. T-cell blasts from beta 2m-deficient (beta 2m -/-) mice were killed by NK cells from normal mice in vitro, while beta 2m +/- blasts were resistant. The beta 2m defect also affected the NK effector cell repertoire: NK cells from beta 2m -/- mice failed to kill beta 2m -/- blasts, while they retained the ability to kill the prototype NK cell target lymphoma YAC-1, although at reduced levels. The inability to recognize beta 2m -/- blasts could be transferred with beta 2m -/- bone marrow to irradiated beta 2m-expressing mice. In contrast, the development of CD8+ T cells (deficient in beta 2m -/- mice) was restored in such chimera. These results indicate that loss of MHC class I/beta 2m expression is sufficient to render normal cells sensitive to NK cells, and that the same defect in the hemopoietic system of a mouse renders its NK cells tolerant to beta 2m-deficient but otherwise normal cells. In the beta 2m -/- mice, NK cells may be selected or educated by other bone marrow cells to tolerate the MHC class I deficiency. Alternatively, the specificity may be controlled directly by the class I molecules on the NK cells themselves.